1995
DOI: 10.1002/ijc.2910640310
|View full text |Cite
|
Sign up to set email alerts
|

c‐erbb growth‐factor‐receptor proteins in ovarian tumours

Abstract: Immunohistochemical expression of EGF-R, c-erbB-2 and c-erbB-3, members of the type-1 family of receptor tyrosine kinases, were investigated in 67 primary ovarian-tumour samples (46 malignant, 8 borderline and 13 benign), and related to tumour clinicopathological features. The incidence of all 3 receptor proteins was highest in overtly malignant tumours. No significant correlations were observed between either EGF-R or c-erbB-3 and clinical parameters such as tumour stage, differentiation or extent of debulkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…Similar results were obtained for breast carcinoma, i.e., c-erbB-3 is related to tumour size and tumour type prognostic group (Travis et al, 1996), and for colorectal carcinoma, i.e., cases without c-erbB-3 expression show a favourable outcome for DFS of the patients (Kapitanovic et al, 2000). On the other hand, such relationships have not been found with other neoplasms such as carcinoma of the esophagus (Freiss et al, 1999), stomach (Sanidas et al, 1993) and ovary (Simpson et al, 1995). In the prostate, a recent study demonstrated the frequent expression of c-erbB-3 in prostatic intraepithelial neoplasia as well as prostatic carcinoma, suggesting that c-erbB-3 plays a role in the carcinogenesis of this carcinoma (Haussler et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar results were obtained for breast carcinoma, i.e., c-erbB-3 is related to tumour size and tumour type prognostic group (Travis et al, 1996), and for colorectal carcinoma, i.e., cases without c-erbB-3 expression show a favourable outcome for DFS of the patients (Kapitanovic et al, 2000). On the other hand, such relationships have not been found with other neoplasms such as carcinoma of the esophagus (Freiss et al, 1999), stomach (Sanidas et al, 1993) and ovary (Simpson et al, 1995). In the prostate, a recent study demonstrated the frequent expression of c-erbB-3 in prostatic intraepithelial neoplasia as well as prostatic carcinoma, suggesting that c-erbB-3 plays a role in the carcinogenesis of this carcinoma (Haussler et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Thus far, of the four receptors, the expression of EGF-R and c-erbB-2 has been investigated in various neoplasms, including malignancies of the liver and biliary tract (Brunt and Swanson, 1992;Collier et al, 1992;Nakapoulou et al, 1994;Lee and Pirdas, 1995;Kira et al, 1997;Terada et al, 1998). The other two receptors, c-erbB-3 and c-erbB-4, have only been studied in depth for a few neoplasms (Sanidas et al, 1993;Simpson et al, 1995;Shintani et al, 1995;Haugen et al, 1996;Travis et al, 1996;Bobrow et al, 1997;Bodey et al, 1997;Chow et al, 1997;Ibrahim et al, 1997;Srinivasan et al, 1998Srinivasan et al, , 2000Suo et al, 1998;Freiss et al, 1999;Haussler et al, 1999;Kapitanovic et al, 2000;Kew et al, 2000), and little is known about their expression in hepatic malignancies. In this study, we investigated the expression of all four components of this family in a large series of HCC to evaluate their clinical significance and to identify the factors reflecting the development of this carcinoma.…”
mentioning
confidence: 99%
“…237 ERBB3, as well as NRG, is expressed in the majority of ovarian tumors, with highest frequency in carcinomas. [238][239][240][241][242][243][244][245] Although greatest expression was reported in early-stage or more differentiated tumors, 239-241 association of ERBB3 with poor prognosis has also been reported, for transitional cell carcinoma 240 and endometrioid cancers. 237 It has recently been confirmed that high ERBB3 expression in ovarian cancer correlates with poor survival.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Of these, 3 receptors, that is, HER -2, HER -3, and HER -4, are involved as HRG -related receptors. Past literature regarding HER (ErbB) receptors reported that multiple types of HER receptors were more frequently expressed in malignant tumors and advanced cancer than in benign tumors and borderline malignancies, significantly influencing tumor invasion and progression 15) . Notwithstanding the above findings, the specific mechanism responsible for the abnormal growth of cancer cells still remains unclear 16) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ovarian cancer, it has been reported that HER -2 overexpression was noted in 71% of the patients with stage 3 advanced cancer 29) . And in those with recurrent ovarian cancer after chemotherapy 30) , but the extent of the association between HER -2 overexpression and the prognosis for the disease still remains mostly unclear 15,25,31,32) . Unfortunately, in a report of the result of a clinical study by Michael A et al in 2003, the response rate of treatment with Trastuzumab alone was low at 7.3% 36) .…”
Section: Discussionmentioning
confidence: 99%